AGRICULTURE AS A PREREQUISITE FOR SUSTAINABLE RURAL TOURISM IN THE DANUBE REGION - Снежана Штетић; Дарио Шимичевић (Ekonomika Poljoprivrede (1979), 2011)
Agriculture and forestry use most of the land in rural areas and play a key role in managing natural resources and rural landscape setting. Agriculture and tourism provide socio-economic development of rural areas and the full realization of their potential, and are the basis of economic diversifcation in rural communities, in addition to tourism and agriculture influence the design direction of a more balanced picture of territorial tourism, development of new reception facilities and creating new offerings in the world tourism market. Linking agriculture and tourism has a large number of effects that can be achieved through the implementation of rural tourism development. The basis of all rural households in which the infrastructure is the starting point for guests in a rural area. Given that the current situation in agricultural households in the negative aspects of age structure and size of farms, and from an economic viewpoint, this means that you can not keep up in the specialization or globalization in the sector. Therefore, the basis for sustainable development in Serbia as a whole and the Danube region is the sustainability of these activities, about which authors and writing in this paper.